Changes in industry and services sectors in Poland during the COVID-19 pandemic - Rachwał, Tomasz; Dominiak, Joanna (Quaestiones Geographicae, 2022)
In 2020, the World Health Organization announced the global COVID-19 pandemic, which was followed by unprecedented constraints on society and the economy. The restrictions imposed had an impact on the transformation in industry and services sectors. The pandemic, however, affected particular industry sections and types of services to a different degree. Overall, the industry sector is assumed to have been less affected by the crisis, because the government restrictions did not embrace industrial production for the most part. Services faced a different situation; some of them were not provided due to top-down decisions. Therefore, the vulnerability of industry and services to such a strong external impact varies. The article aims to identify the degree and trends in changes in industry and services sectors during the COVID-19 pandemic and to determine the regularities stemming from a different degree of vulnerability of both sectors to such a powerful external stimulus. The study examines changes occurring in different industries and types of services (by the Polish Classification of Economic Activity/NACE 2.0) by way of statistical indicator analysis and using Statistics Poland and Eurostat data. The conducted analysis of the COVID-19 pandemic influence on the industry and services sector leads to the conclu- sions that its impact on the industry sector was very time-limited—a sharp fall in gross value added in industry oc- curred mainly in the second quarter of 2020. The pandemic had a modest effect on industry employment, primarily as a result of anti-crisis shields and the will to maintain the potential of labour resources. In the services sector, accommo- dation and food services suffered the most. The significant falls were noted in the transport section as well as cultural, sports and personal services. Business services which were transferred to the Internet and were provided online ended up the most resilient. The ultimate winner of the pandemic is ICT services, especially electronic ones, which have re- placed, wherever possible, traditional types of services.